1977
DOI: 10.1098/rstb.1977.0033
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical approaches to the intermolecular nature of water

Abstract: A brief review is presented of recent advances in theoretical understanding of liquid water. These advances include detailed quantitative specification of water-molecule interaction potentials, and development of several techniques in statistical mechanics for predicting molecular order in the liquid. Specifically, computer simulation now plays a particularly important rôle. A labile, defective, random network picture for the liquid is the only consistently supported possibility. Implications of this picture f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 40 publications
(32 reference statements)
1
6
0
Order By: Relevance
“…The lower the temperature, the stronger this distortional effect of the applied pressure seems to be. This is consistent with the view that strong supercooling leads to an increased straightening of 0 -H ..O-bonds in the random hydrogen bonded network and that the major effect of pressure in the low pressure region is to deform hydrogen bond angles [42,43]. This tendency is not found at higher pressures.…”
Section: ) Estimate Of the Deuterium Quadrupole Coupling Constant ( supporting
confidence: 90%
“…The lower the temperature, the stronger this distortional effect of the applied pressure seems to be. This is consistent with the view that strong supercooling leads to an increased straightening of 0 -H ..O-bonds in the random hydrogen bonded network and that the major effect of pressure in the low pressure region is to deform hydrogen bond angles [42,43]. This tendency is not found at higher pressures.…”
Section: ) Estimate Of the Deuterium Quadrupole Coupling Constant ( supporting
confidence: 90%
“…There are several approaches that estimate the lifetime directly from this probability function (i.e., the “intermittent” approach , ). In contrast, the reactive flux method eliminates perturbations from diffusion with the aid of a second state in which the pair of interest is not connected by a hydrogen bond but is still within a distance that a hydrogen bond could be reformed.…”
Section: Reactive Flux Approachmentioning
confidence: 99%
“…(1) All-atom models and convergence problems The pioneering simulation of the properties of liquid water by Barker & Watts (1969) and by Stillinger & Rahman (Rahman & Stillinger, 1971;Stillinger & Rahman, 1974;Stillinger, 1977) and subsequent studies (Watts, 1974;McDonald & Klein, 1978;Owicki & Scheraga, 1977;van Gunsteren, Berendsen & Rullman, 1978;Barnes et al 1979;Berendsen et al 1981;Jorgensen, 1981Jorgensen, , 1982Mezei & Beveridge, 1982;Berens etal. 1983;White & Wilson, 1984) have demonstrated that pure polar solvents can be simulated in a computationally manageable way.…”
Section: (B) Simulating Electrostatic Energies In Polar Solventsmentioning
confidence: 99%